Porphyromonas gingivalis in dental plaque and serum C-reactive protein levels in pregnancy - Souccar, Nada M.; Chakhtoura, Marita; Ghafari, Joseph G.; Abdelnoor, Alexander Michael (The Journal of Infection in Developing Countries, 2010)
Background: The periodontopathogen Porphyromonas gingivalis (Pg) has been reported as a risk factor for preterm labour. Its pathogenesis and role in pregnancy have not been investigated in Lebanon. Elevated C-reactive protein (CRP) levels in pregnant women with periodontitis also appear to mediate preterm labour. Methodology: The study included 20 pregnant women with periodontitis and 20 with normal periodontium. PCR was done for Pg detection in oral plaque and vaginal samples. Serum CRP levels were determined by ELISA. Results: Pg was detected in the oral plaque of 13 of 20 pregnant subjects with clinical periodontitis (patients) and 2 of 20 controls with a healthy periodontium. Vaginal swabs were all Pg-negative, ruling out systemic infection. Serum CRP levels were elevated in 12 of 20 patients and 8 of 20 controls. None of the participants experienced preterm labour. Conclusions: This is the first report that implicates Pg in Lebanese periodontitis patients. Preliminary results do not indicate a relationship among Pg, periodontitis, CRP levels and preterm labour.